Investigating Character-Building Values in English Textbook Entitled Bahasa Inggris for Grade X - Nabilla Puspa Amelia; Sudarya Permana (Stairs, 2021)
This research aims to investigate (1) the character-building values presented in the English textbook entitled Bahasa Inggris for grade X, and (2) the way character-building values were presented into its materials. The researcher referred to 18 character-building values mandated by the Ministry of National Education (2010). This research used a qualitative research method using content analysis. The data used in this research were the sentences contained in this textbook. The results showed that the English textbook entitled Bahasa Inggris for grade X contained all the character-building values, the most of which was the friendly/communicative value with percentage of 16% and the least of which was the tolerance value with percentage of 1%. There were two techniques of integrating characters that were found in the textbook, namely explicit and implicit techniques. The results of this study are expected to be able to give instances to the English teachers so that they can appropriately give these characters to students and be more selective in choosing a textbook or a learning method.